A retrospective study of neoadjuvant chemotherapy plus radical hysterectomy versus radical hysterectomy alone in patients with stage II cervical squamous cell carcinoma presenting as a bulky mass - Takatori, Eriko (Onco Targets Ther, 2016)
OBJECTIVE: In order to evaluate the usefulness of neoadjuvant chemotherapy (NAC) for stage II cervical squamous cell carcinoma with a bulky mass, we retrospectively compared patients receiving NAC followed by radical hysterectomy (RH; NAC group) with patients who underwent RH without NAC (Ope group). PATIENTS AND METHODS: The study period was from June 2002 to March 2014. The subjects were 28 patients with a stage II bulky mass in the NAC group and 17 such patients in the Ope group. The chi-square test was used to compare operative time, volume of intraoperative blood loss, use of blood transfusion, and time from surgery to discharge between the two groups. Moreover, the log-rank test using the Kaplan–Meier method was performed to compare disease-free survival (DFS) and overall survival (OS) between the groups. RESULTS: There were no statistically significant differences between the two groups in operative time, volume of intraoperative blood loss, or use of blood transfusion. However, the time from surgery to discharge was 18 days (14–25 days) in the NAC group and 25 days (21–34 days) in the Ope group; the patients in the NAC group were discharged earlier (P=0.032). The hazard ratio for DFS in the NAC group as compared with that in the Ope group was 0.36 (95% CI 0.08–0.91), and the 3-year DFS rates were 81.2% and 41.0%, respectively (P=0.028). Moreover, the hazard ratio for OS was 0.39 (95% CI 0.11–1.24), and the 3-year OS rates were 82.3% and 66.4%, respectively (P=0.101). CONCLUSION: NAC with cisplatin and irinotecan was confirmed to prolong DFS as compared with RH alone. The results of this study suggest that NAC might be a useful adjunct to surgery in the treatment of stage II squamous cell carcinoma presenting as a bulky mass.